The Profitability of Dutch Business in Late Colonial Indonesia - Jan Thomas Lindblad (Universitas Gadjah Mada, 2018)
The issue of profitability of colonial business lies at the core of the argument about a possible colonial drain depriving the overseas territory of opportunities to selfsustained economic growth. This contribution seeks to assess whether profit rates of private foreign firms in the colonial economy can be considered excessive or a reasonable compensation for capital and know-how made available to the colony. The article contains brief sections on historiography and methodology as well as new estimates, including a preliminary discussion of results. The article argues that profit rates in colonial business were generally higher than elsewhere, but also that the difference was smaller than has often been imagined.